2016
DOI: 10.1371/journal.pone.0160826
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure of Rats to Isoflurane during Late Pregnancy Impairs Spatial Learning and Memory in the Offspring by Up-Regulating the Expression of Histone Deacetylase 2

Abstract: Increasing evidence indicates that most general anesthetics can harm developing neurons and induce cognitive dysfunction in a dose- and time-dependent manner. Histone deacetylase 2 (HDAC2) has been implicated in synaptic plasticity and learning and memory. Our previous results showed that maternal exposure to general anesthetics during late pregnancy impaired the offspring’s learning and memory, but the role of HDAC2 in it is not known yet. In the present study, pregnant rats were exposed to 1.5% isoflurane in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…It is relevant that HDAC2 does not interact with NF‐κB directly but can regulate NF‐κB activity through its association with HDAC1 . By contrast, several other studies have found that repeated isoflurane exposure enhances the expression of inflammatory cytokines in the brain with HDAC2 upregulation . Our results combined with those of previous studies support the idea that isoflurane‐induced histone deacetylation and inhibition of NF‐κB nuclear translocation and inflammatory genes could contribute to the anti‐inflammatory properties of isoflurane.…”
Section: Discussionsupporting
confidence: 81%
“…It is relevant that HDAC2 does not interact with NF‐κB directly but can regulate NF‐κB activity through its association with HDAC1 . By contrast, several other studies have found that repeated isoflurane exposure enhances the expression of inflammatory cytokines in the brain with HDAC2 upregulation . Our results combined with those of previous studies support the idea that isoflurane‐induced histone deacetylation and inhibition of NF‐κB nuclear translocation and inflammatory genes could contribute to the anti‐inflammatory properties of isoflurane.…”
Section: Discussionsupporting
confidence: 81%
“…Abolished the memory impairments in connection with neurodegeneration 35. Our earlier study suggested that maternal isoflurane anaesthesia during third trimester impairs the spatial learning and memory of the offspring rats, and its mechanism in connection with the up‐regulation of HDAC2 mRNA and subsequent inhibits the expression of CREB mRNA and NR2B, while HDAC2 inhibition reversed these changes 30. Consistent to our previous study, our results suggest that maternal propofol anaesthesia on E7 impairs learning and memory in offspring rats, causes the overexpression of HDAC2 and inhibits the acetylation of H3K14 and H4K12, and these effects were reversed by SAHA.…”
Section: Discussionmentioning
confidence: 94%
“…Spatial learning and memory were assessed by the MWM test from post‐natal day 30 (P30) to P36 according to previously described5, 30 with SLY‐WMS Morris water maze test system (Beijing Sunny Instruments Co. Ltd., Beijing, China). Briefly, the trials start at 9 o'clock in the morning in the MWM system with the pool was filled with water to a height of 1.0 cm above the top of a 15‐cm‐diameter platform, in the second quadrant (target quadrant), and the water maintained at 24 ± 1°C.…”
Section: Methodsmentioning
confidence: 99%
“…Offspring of pregnant rat exposed with isoflurane anesthesia showed impaired spatial memory with increase in HDAC2 and decrease in CREB and NR2B expression in the hippocampus. Further, treatment with HDAC inhibitor Suberoylanilide hydroxamic acid (SAHA) ameliorated the effect of isoflurane and recovered memory in offspring [ 89 ]. Maternal separation is an early life stress which has adverse effect on nervous system of the young and impaired cognitive functions including learning and memory.…”
Section: Chromatin Modifications and Regulation Of Memorymentioning
confidence: 99%